2015
DOI: 10.1097/qai.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Contraceptive Use Among Women Participating in the FEM-PrEP Trial

Abstract: Women using COCs during FEM-PrEP, particularly new adopters, were more likely to become pregnant and less likely to adhere to study product than injectable users. HIV prevention trials should consider requiring long-acting methods, including injectables, for study participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
2
35
1
Order By: Relevance
“…Nevertheless, as Callagan et al, it appears to interfere with oral contraceptives, and unwanted pregnancies were found among users of oral contraceptives who had received PrEP [16].…”
Section: Resultsmentioning
confidence: 90%
“…Nevertheless, as Callagan et al, it appears to interfere with oral contraceptives, and unwanted pregnancies were found among users of oral contraceptives who had received PrEP [16].…”
Section: Resultsmentioning
confidence: 90%
“…Analyses of two large trials of hormonal contraceptives and NRTIs used for PrEP found that use of tenofovir/emtricitabine did not affect pregnancy rates among users of COCs, injectables, or implants [40,41]. …”
Section: Resultsmentioning
confidence: 99%
“…This rate of pregnancy loss has been seen in other studies with sensitive testing that detects early pregnancy [15]. Two additional PrEP clinical trials, FEM-PrEP conducted among 2,120 women in Kenya, South Africa, and Tanzania and VOICE among 3,019 women from South Africa, Zimbabwe, and Uganda, observed substantial numbers of pregnancies among women randomized to active PrEP agents as well as placebo and observed no indications of pregnancy-related safety concerns among those in the active PrEP arms [12, 13, 16, 17]. However, adherence to daily PrEP medication was extremely low in these two trials and results based on randomization arm would be better supplemented by data from the subgroup of women who were highly adherent [16, 17].…”
Section: Peri-conception Prep Use – Including Use During Early Pregnamentioning
confidence: 88%